The relationship between status anxiety and loneliness with well-being in a neoliberal society: Analysis of a Spanish sample - Canto-Ortiz, Jesús María; García-Martín, Miguel Ángel; Vallejo-Martín, Macarena (Universidade de São Paulo, Faculdade de Filosofia Ciências e Letras de Ribeirão Preto, 2025)
Social psychology has recently shown increasing interest in analysing the influence of neoliberalism on individual psychology. In this study, we examine in a Spanish sample whether levels of status anxiety and loneliness are negatively associated with well-being as individuals perceive their country’s economic policies to be increasingly neoliberal in nature. A total of 343 participants (205 women, 138 men) took part in the study. Results indicated that status anxiety and loneliness sequentially mediate the relationship between neoliberalism and well-being. Perceived neoliberalism was found to be positively related to both status anxiety and loneliness. Additionally, loneliness was negatively associated with well-being. The findings highlight that one of the ways in which status anxiety is negatively related to well-being in individuals who perceive high levels of neoliberalism is through increased loneliness.
A relação entre a ansiedade de status e a solidão com o bem-estar numa sociedade neoliberal: Análise de uma amostra espanhola
Keywords: Neoliberalismo; Economía - Aspectos psicológicos; Health; Loneliness; Anciety; Ideology